1996
DOI: 10.1136/emj.13.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Primary care in London: an evaluation of general practitioners working in an inner city accident and emergency department.

Abstract: The demand for primary care at St Mary's necessitates the provision of a primary care service, albeit for the first visit only. This can be provided by GPs in A&E. The features of the patients using the service suggests that discouraging first attendance is unrealistic, but using the visit to educate patients and return them to the care of the community is not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 8 publications
0
67
0
Order By: Relevance
“…It also seems to be cost-effective. 7,8 A possible disadvantage of this innovation is that GPs who work directly within an ED may adjust their own medical practice to fit in with common ED practices. Westert 9 showed that specialists choose different lengths of stay when working in different hospitals, thereby demonstrating that setting affects behavior.…”
Section: Innovationsmentioning
confidence: 99%
“…It also seems to be cost-effective. 7,8 A possible disadvantage of this innovation is that GPs who work directly within an ED may adjust their own medical practice to fit in with common ED practices. Westert 9 showed that specialists choose different lengths of stay when working in different hospitals, thereby demonstrating that setting affects behavior.…”
Section: Innovationsmentioning
confidence: 99%
“…United Kingdom studies confirm that GP hospitals save costs by reducing referrals and admissions to higher-cost general hospitals staffed by specialists (57,58,59). Care delivered by general practitioners, compared to hospital specialists, in hospital-based accident and emergency departments was shown to be more cost effective with lower use of diagnostic investigations, lower referral rates to secondary services, lower prescription levels, and no significant difference in patient satisfaction or health outcomes (60,61,62).…”
Section: Cost Effectivenessmentioning
confidence: 80%
“…Most of the included citations were variations on an uncontrolled before and after study, with one quasi-randomised evaluation,10 two randomised controlled trials (RCTs)11 12 and one pragmatic prospective evaluation 13…”
Section: Resultsmentioning
confidence: 99%
“…Six studies10 12 13 18 19 21 reported more diagnostic testing (predominantly radiography and blood tests) by ED clinicians than GPs in the ED or adjacent service. One study using GPs within the ED11 found no difference in the use of investigations (RR 1.06; 95% CI 1.00 to 1.13) between ED and GP clinicians.…”
Section: Resultsmentioning
confidence: 99%